Fresh Frozen Plasma in Cases of Acute Upper Gastrointestinal Bleeding Does Not Improve Outcomes - Liu, Shuang; Zhang, Xiaoming; Walline, Joseph Harold; Yu, Xuezhong; Zhu, Huadong (Frontiers in Medicine, 2022)
Background: Blood products are commonly transfused in patients with acute upper gastrointestinal bleeding (UGIB). There exists considerable practice variation and little evidence to guide fresh frozen plasma (FFP) transfusion in UGIB patients. The aim of this study was to explore any association between FFP transfusion following acute UGIB and clinical outcomes. Methods: This was a prospective observational multicentre study conducted at 20 tertiary hospitals in China. Patients with acute UGIB with an international normalized ratio (INR) ≤2.0 at emergency department (ED) admission were included. Multivariate logistic regression models were used to examine and quantify any clinical associations. Results: A total of 976 patients (61.57 ± 15.79 years old, 73.05% male) were included, of which 17.42% received an FFP transfusion. The overall 90-day mortality and rebleeding rates were 10.2% and 12.19%, respectively. After adjusting for confounding factors, transfusion of FFP during hospitalization was associated with higher 90-day mortality (odd ratio [OR], 2.36; 95% confidence interval [CI], 1.36-4.09; P=0.002) but not rebleeding (OR, 1.5; 95% CI; 0.94-2.54; P=0.085). In a subgroup analysis, patients with an INR<1.5 who were treated with FFP were associated with both significantly higher 90-day mortality (OR, 2.78; 95% CI, 1.49-5.21; P=0.001) and rebleeding (OR, 2.02; 95% CI, 1.16-3.52; P=0.013), whereas in patients with an INR between 1.5-2, we did not find any significant correlation. Conclusion: This study found an association between FFP transfusion following acute UGIB and elevated 90-day mortality. Both 90-day mortality and rebleeding risk were significantly higher in patients with an INR<1.5. FFP transfusion in acute upper gastrointestinal bleeding does not improve the poor outcomes (Chinese Clinical Trial registry, Number ChiCTR1900028676)